Weakly $M$-preopen functions in biminimal structure spaces - Basumatary, A.A.; Sarma, D.J.; Tripathy, B.C. (Carpathian Mathematical Publications, 2023)
The intention of this article is to define the concept of weakly $M$-preopen function in biminimal structure spaces. Several properties of this function have been established and its relationship with some other notions related to $M$-preopen sets in biminimal spaces have been investigated.